Ibrutinib Has Time-dependent On- and Off-target Effects on Plasma Biomarkers and Immune Cells in Chronic Lymphocytic Leukemia. Issue 5 (26th May 2021) - Mulder, Tom A.; Peña-Pérez, Lucía; Berglöf, Anna; Meinke, Stephan; Estupiñán, H. Yesid; Heimersson, Kia; Zain, Rula; Månsson, Robert; Smith, C. I. Edvard; Palma, Marzia
Abstract : Supplemental Digital Content is available in the text. Abstract : Ibrutinib is a covalently binding inhibitor of the B-cell receptor signaling-mediator Bruton's tyrosine kinase (BTK) with great efficacy in chronic lymphocytic leukemia (CLL). Common side effects like atrial fibrillation (AF), bleeding and infections might be caused by ibrutinib's inhibition of other kinases in non-B cells. Five-year follow-up of plasma biomarkers by proximity extension assay and immune cell numbers by flow cytometry during ibrutinib treatment revealed that 86 of the 265 investigated plasma biomarkers significantly changed during treatment, 74 of which decreased. Among the 12 markers that increased, 6 are associated with cardiovascular diseases and therefore potentially involved in ibrutinib-induced AF. Comparison between healthy donors and X-linked agammaglobulinemia (XLA) patients, who have nonfunctional BTK and essentially lack B cells, showed indicative changes in 53 of the 265 biomarkers while none differed significantly. Hence, neither B cells nor BTK-dependent pathways in other cells seem to influence the levels of the studied plasma biomarkers in healthy donors. Regarding immune cells, the absolute number of T cells, including subsets, decreased, paralleling the decreasing tumor burden. T helper 1 (Th1) cell numbers dropped strongly, while Th2 cells remained relatively stable, causing Th2-skewing. Thus, long-term ibrutinib treatment has a profound impact on the plasma proteome and immune cells in patients with CLL.